(untitled) (Raparin Journal of Humanities (RJH), 2023)
The study, entitled "Sculpture Beauty in the Fields of the Kurdistan Region," found and selected sculptural samples that have been stabilized in the fields of the Kurdistan Region, and analyzed the samples to determine whether they are the bearers of a sculpture. The research consists of four sections, the first part consists of the theoretical framework in which the problem of research and the importance of research and the boundaries of research and the concepts of ministries are addressed, the second part consists of three layers, the first layer (explaining the meaning and concept of beauty). (Explaining the concept of discourse in the modeling pantheon) The third layer consists of (an introduction to the field in the stages of ancient history and modern times). The stabilized ones, which are numbered (2), can be described by the method of descriptive analysis. Results and conclusions of recommendations, suggestions and sources) of the study.